Examining the Influence of Cyberbullying Perpetration and Victimization among High School Adolescents-Associations with Gender and Grade Level - Ramazan Yirci; Turgut Karakose; Nedim Malkoc (ÜNİVERSİTEPARK Limited, 2021)
Background/purpose - The present study examined adolescent students' cyberbullying behavior and being a victim of cyberbullying specifically exploring potential differences by gender and grade level. Materials/methods - Based on a cross-sectional survey on 311 adolescent students continuing their high school education in secondary education institutions in Turkey, the study reported their findings as with differences between gender and grade level in cyberbullying and cyber victimization. The research data was obtained by using the Likert-type "Cyberbully/Cyber-victim Scale." Together with statistics, t-test, ANOVA and Tukey's b test were applied the analysis of the collected data. Results - The study's results suggest a significant difference in the level of students displaying cyberbullying behaviors and being exposed to them within virtual platforms with regards to the gender variable. Male students display cyberbullying behaviors and are also exposed to them in virtual platforms more than female students. In addition, the study's results reveal that female students tend to rumor (gossip) more than male students on virtual platforms. There was also a significant difference in the level of participants performing and being exposed to cyberbullying behaviors on virtual platforms with regards to the grade level variable. According to the analyzed data, students from higher grade levels both perform cyberbullying behaviors more and are more frequently exposed to cyberbullying than students from lower grade levels. In other words, in higher grade levels, students' performance of, and exposure levels to, cyberbullying was found to increase. Conclusion - This study's findings emphasize the importance of developing prevention and intervention strategies must be developed in order to fight cyberbullying in schools when investigating the level of high school adolescents' bullying of their peers, and the level of those exposed to cyberbullying.